Digital stethoscope - Kishen Sivayam Yoga Raja (2017)
Stethoscopes are an inseparable part of clinical examination in hospitals. It helps in auscultation, i.e., to check a patient's health conditions through audible sounds originating from inside body. Since properties of a human ear vary from person to person, it may be prone to error. So in order to aid a doctor, digital stethoscopes are born. The sound signals once converted to electronic signals can be used to study its features to separate various abnormal heart sounds. This project involves the construction of a digital stethoscope using electronic components for collection of heart sounds.